'The life of crime does not pay; stop and think!': the process of co-constructing a prototype pedagogical model of sport for working with youth from socially vulnerable backgrounds. (4th July 2017) - Luguetti, Carla; Oliver, Kimberly L.; Dantas, Luiz E.P.B.T.; Kirk, David
ABSTRACT: Purpose : This study discusses the process of co-constructing a prototype pedagogical model for working with youth from socially vulnerable backgrounds. Participants and settings : This six-month activist research project was conducted in a soccer program in a socially vulnerable area of Brazil in 2013. The study included 17 youths, 4 coaches, a pedagogic coordinator and a social worker. An expert in student-centered pedagogy and inquiry-based activism assisted as a debriefer helping in the progressive data analysis and the planning of the work sessions. Data collection/analysis : Multiple sources of data were collected, including 38 field journal/observation and audio records of: 18 youth work sessions, 16 coaches' work sessions, 3 combined coaches and youth work sessions, and 37 meetings between the researcher and the expert. Findings : The process of co-construction of this prototype pedagogical model was divided into three phases. The first phase involved the youth and coaches identifying barriers to sport opportunities in their community. In the second phase, the youth, coaches and researchers imagined alternative possibilities to the barriers identified. In the final phase, we worked collaboratively to create realistic opportunities for the youth to begin to negotiate some of the barriers they identified. In this phase, the coaches and youth designed an action plan to implement (involving a Leadership Program) aimed at addressing the youths' needs in the sport program. Five critical elements of a prototype pedagogical model were co-created through the first two processes and four learning aspirations emerged in the last phase of the project. Implications : We suggest an activist approach of co-creating a pedagogical model of sport for working with youth from socially vulnerable backgrounds is beneficial. That is, creating opportunities for youth to learn to name, critique and negotiate barriers to their engagement in sport in order to create empowering possibilities.